The Influence of Occupational Health and Safety (OHS), Compensation, and the Work Environment on Employee Performance at CV. Bali Treasures Gianyar - Ni Putu Ayu Tika Kurniawati; Ni Ketut Ari Krisna Dewi (Journal of Governance, Taxation and Auditing, 2026)
This study was conducted based on a research gap identified in previous studies and differing perspectives regarding the impact of occupational health and safety (OHS), compensation, and the work environment on employee performance. Additionally, a research problem was identified wherein revenue realization had failed to meet the targets established by the company. This study aims to examine and analyze the influence of occupational health and safety (OHS), compensation, and the work environment on employee performance. The study was conducted at CV. Bali Treasures with a sample of 70 respondents selected using a saturated sampling method. All data obtained from the distributed questionnaires were deemed valid and subsequently analyzed using multiple linear regression and hypothesis testing (t-test and F-test). The results indicate that (1) Occupational health and safety (OHS), compensation, and the work environment have a positive and significant effect on employee performance at CV. Bali Treasures; (2) Occupational health and safety (OHS) has a positive and significant effect on employee performance at CV. Bali Treasures, meaning that improvements in OHS lead to enhanced employee performance; (3) Compensation has a positive and significant effect on employee performance at CV. Bali Treasures, meaning that increased compensation leads to enhanced employee performance; and (4) The work environment has a positive and significant effect on employee performance at CV. Bali Treasures, meaning that a more conducive work environment leads to enhanced employee performance.